2023
DOI: 10.1039/d3ee00045a
|View full text |Cite
|
Sign up to set email alerts
|

Selection criteria for electrical double layer structure regulators enabling stable Zn metal anodes

Abstract: Regulating the electrical double layer (EDL) structure via electrolyte additives is a promising strategy to improve the cycle stability of Zn anodes, but there are no general disciplines that can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 65 publications
2
47
0
Order By: Relevance
“…As displayed in Figure S4, the decrease in the EDL capacitance of the ZnSO 4 -80 Gly electrolyte manifested that the Gly ± tends to expand the thickness of the EDL on the Zn surface capable of weakening the EDL repulsion. 40,41 Moreover, Fourier transform infrared (FTIR) spectra (Figure S5) of Zn metal foil immersed in ZnSO 4 -80 Gly electrolytes show almost no distinct characteristic peak of H 2 O (3200−3400 cm −1 ) 42 and SO 4 2− (1123 cm −1 ), 43,44 but obvious characteristic peaks of the C�O stretching vibration, N−H bending vibration, and C−N stretching vibration appeared at 1643, 1519, and 1020 cm −1 . 45 Then, the X-ray diffraction (XRD) pattern and scanning electron microscopy (SEM) image (Figure S6) of the Zn foil immersed in ZnSO 4 -80 Gly electrolyte depicted the absence of the byproduct (Zn 4 SO 4 (OH) 6 •xH 2 O) diffraction peak at 8.1°a nd no hexagonal sheets or defects on the surface of the Zn metallic foil.…”
Section: Resultsmentioning
confidence: 99%
“…As displayed in Figure S4, the decrease in the EDL capacitance of the ZnSO 4 -80 Gly electrolyte manifested that the Gly ± tends to expand the thickness of the EDL on the Zn surface capable of weakening the EDL repulsion. 40,41 Moreover, Fourier transform infrared (FTIR) spectra (Figure S5) of Zn metal foil immersed in ZnSO 4 -80 Gly electrolytes show almost no distinct characteristic peak of H 2 O (3200−3400 cm −1 ) 42 and SO 4 2− (1123 cm −1 ), 43,44 but obvious characteristic peaks of the C�O stretching vibration, N−H bending vibration, and C−N stretching vibration appeared at 1643, 1519, and 1020 cm −1 . 45 Then, the X-ray diffraction (XRD) pattern and scanning electron microscopy (SEM) image (Figure S6) of the Zn foil immersed in ZnSO 4 -80 Gly electrolyte depicted the absence of the byproduct (Zn 4 SO 4 (OH) 6 •xH 2 O) diffraction peak at 8.1°a nd no hexagonal sheets or defects on the surface of the Zn metallic foil.…”
Section: Resultsmentioning
confidence: 99%
“…To date, ZnSO 4 and Zn(CF 3 SO 3 ) 2 are widely utilized as electrolyte solutions in aqueous ZIBs owing to their relatively wide electrochemical windows. [232,233] As indicated in the previous introduction, other solutions like ZnCl 2 , Zn(CH 3 COO) 2 , and Zn(NO 3 ) 2 are explored actively as well. While ZnSO 4 exhibits superiority performance due to the SO 4 2− having higher stability and compatibility than other anions, which brings in faster reaction kinetics.…”
Section: Electrolyte Enhancementmentioning
confidence: 99%
“…Reportedly, aromatic conjugate structures and amino groups promote the preferential adsorption of 0.5 vol % sulfolane on Zn anode interface and reduction decomposition of additive molecules facilitates the formation of stable SEI. [53] Chen et al demonstrated SEI forming capability as the most important feature for high-performance EDL regulators in trace (< 1.0 vol.%) additives (Figure 5e). Conclusively, the rational design of EDL regulators needs to be explored for improvement in anode performance.…”
Section: Organic Moleculesmentioning
confidence: 99%